Trade as an Engine of Grow in Somalia : Constraints and Opportunities - World Bank (World Bank, Washington, DC, 2021)
International trade can promote efficiency, knowledge diffusion, technological progress, and—what ultimately matters most—inclusive growth and poverty reduction. Boosting export competitiveness is inextricably linked with rebuilding the productive sectors of Somalia’s economy, generating jobs and incomes, and reducing the country’s large structural trade deficits, which have averaged over 80 percent of GDP since 2015. Somalia supplies a limited number of exports to a relatively small set of markets. Its top five export products in 2018 accounted for more than 83 percent of total goods exports. Dominated by live animals, these exports are primarily unprocessed primary commodities that do not generate spillovers to other sectors of the economy and are vulnerable to weather and other shocks. Somalia also exports to a small set of countries: 82 percent of its exports were sold to just five destinations in 2018, mainly the United Arab Emirates, Oman, and Saudi Arabia. Somalia’s annual goods export revenues could be increased significantly by expanding sales of current exports to new markets and markets where potential remains untapped. Export growth opportunities are greatest for sesame seed and fish. There is also some potential to increase livestock exports by seeking new markets, although econometric analysis suggest that some markets in the Gulf may be saturated. Gums and resins (frankincense and myrrh), fruit, and meat also show potential for increased sales. Countries in East and South Asia present the greatest opportunities for growth. These export opportunities could be prioritized in Somalia’s national trade strategy. Limited or unreliable domestic supply constrains many of Somalia’s exporters. The World Bank’s 2018 Country Economic Memorandum (CEM) presents recommendations for sustainably increasing output of fish, sesame seed, animals, and other commodities that Somalia already exports. To break into new markets, Somali exporters must also invest in gathering information about consumer preferences and policies in unfamiliar markets and establish business relationships with new buyers, shippers, and other partners. The 2018 CEM identifies important roles for public and private sectors in strengthening systems to ensure animal and plant health and developing logistical arrangements to support increased trade flows, which could be reflected in the national trade strategy.